DAS CURRICULUM IN KONZEPTIONELLEN NETZWERKEN UND IN DEREN APPLIKATIONEN (VERWENDUNG)DAS CURRICULUM IN KONZEPTIONELLEN NETZWERKEN UND IN DEREN APPLIKATIONEN (VERWENDUNG) - VASILE CHIŞ; OLGA CHIŞ (Studia Universitatis Babes-Bolyai, 2012)
ABSTRACT. Curriculum in Conceptual Networks and their Applications (Utilization). The content of this article is focused on several contemporary debates on developments in contemporary pedagogy and its impact on school curriculum. Here we included six topics which we founded as being very relevant for today debates: 1. From "Analytical Pedagogies" to the Synthesis in Sciences of Education" 2. Curriculum between concept and application; 3. The need for conceptual clarification; 4. Trends and guidelines for curriculum conceptualization; 5. Types of curricula and their relevance to contemporary education and 6. Pedagogy of curriculum: conceptual framework and application.